THE DEVELOPMENT OF THE LITERACY OF QUR’ᾹNIC INTERPRETATIONS IN SUDAN: CRITICAL STUDY OF THE AL-TAFSĪR AL-TAUḤĪDĪ - Hasan, Moh Abdul Kholiq (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2021)
This article aims to critically explain the method of al-Tafsīr al-Tauḥīdī by Ḥasan al-Turābī and its position amongst other thematic commentary theories. This study is a descriptive qualitative study by employing content analysis theory. The results indicate the trend of al-Tafsīr al-Tauḥīdī in two meanings. The first is as a commentary paradigm which leans on the unity of man and the universe in the message of the God’s revelation. The second is as the form of thematic commentary of al-Waḥdah al-Mauḍū‘iyyah model. Therefore, this commentary is more appropriately categorized into al-Tafsīr al-Muṣhafī bi al-Waḥdah al-Mauḍū’iyyah. It has three systematic explanation in each surah including Khulāṣah Hady al-Sūrah, Tartīl al-Ma’āni, and Umūm al-ma’āni. Al-Turābī's ability to unite various related elements in his commentary is not only between verses or surahs but also between human life and all its activities with the universe in a bond of al-Qur'an guidance which is core to monotheism. This is the advantage it has and is a new method in commentary literacy in Sudan. In fact, the method of al-Tafsīr al-Tauḥīdī generally becomes a framework for the whole civilization project of al-Turābī. However, there are some critics towards his commentary regarding rationality and rejection of several authentic hadiths which seem to leave riwāyah in the commentary of the Qur’an.